2010
DOI: 10.1111/j.1755-3768.2008.01498.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the incidence of early postoperative vitreous haemorrhage by preoperative intravitreal bevacizumab in vitrectomy for diabetic tractional retinal detachment

Abstract: ABSTRACT.Purpose: This study aimed to evaluate whether preoperative intravitreal injection of bevacizumab reduces early postoperative vitreous haemorrhage (VH) in vitrectomy for diabetic tractional retinal detachment. Methods: We conducted a retrospective chart review of a consecutive, interventional case series. This included 29 eyes (27 patients) in the bevacizumab group and 40 eyes (37 patients) in the non-bevacizumab group. For statistical analysis, each patient was assigned to one of four groups according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 32 publications
0
25
1
Order By: Relevance
“…The occurrence of postoperative vitreous hemorrhage tends to be less frequent with the adjuvant use of bevacizumab (18)(19)(22)(23) , although this result was not observed in other studies (21,24,28) . Postoperative vitreous hemorrhage can also be combated with gas buffering, which proved to be as effective as preoperative bevacizumab in a study by Yeung et al (23) , although in that study the best results were obtained with the preoperative use of bevacizumab in combination with gas at the end of vitrectomy. Yang et al (28) suggested that, although the frequency of postoperative vitreous hemorrhage did not differ between groups treated or not with adjuvant bevacizumab in their study, the use of the antiangiogenic drug allowed a more rapid vitreous clearing during the postoperative period.…”
Section: Preoperative Administration Of Anti-vegf Drugs Before Pars Pcontrasting
confidence: 52%
See 4 more Smart Citations
“…The occurrence of postoperative vitreous hemorrhage tends to be less frequent with the adjuvant use of bevacizumab (18)(19)(22)(23) , although this result was not observed in other studies (21,24,28) . Postoperative vitreous hemorrhage can also be combated with gas buffering, which proved to be as effective as preoperative bevacizumab in a study by Yeung et al (23) , although in that study the best results were obtained with the preoperative use of bevacizumab in combination with gas at the end of vitrectomy. Yang et al (28) suggested that, although the frequency of postoperative vitreous hemorrhage did not differ between groups treated or not with adjuvant bevacizumab in their study, the use of the antiangiogenic drug allowed a more rapid vitreous clearing during the postoperative period.…”
Section: Preoperative Administration Of Anti-vegf Drugs Before Pars Pcontrasting
confidence: 52%
“…While some studies have reported a statistically significant postoperative gain of visual acuity in patients previously treated with bevacizumab (18)(19)(22)(23)29) , others did not observe this benefit (20)(21)24,28) . The occurrence of postoperative vitreous hemorrhage tends to be less frequent with the adjuvant use of bevacizumab (18)(19)(22)(23) , although this result was not observed in other studies (21,24,28) . Postoperative vitreous hemorrhage can also be combated with gas buffering, which proved to be as effective as preoperative bevacizumab in a study by Yeung et al (23) , although in that study the best results were obtained with the preoperative use of bevacizumab in combination with gas at the end of vitrectomy.…”
Section: Preoperative Administration Of Anti-vegf Drugs Before Pars Pmentioning
confidence: 93%
See 3 more Smart Citations